Population genetic diversity of sesarmid crab (Perisesarma bidens) in China based on mitochondrial DNA. (2nd September 2016) - Zhou, Haolang; Xu, Jingming; Yang, Mingliu; Wu, Bin; Yan, Bing; Xiong, Yingze
Abstract: The population genetic diversity of Perisesarma bidens in China was investigated using 627 bp fragment of mtDNA COI gene sequence. A total of 186 individuals were collected from ten localities over most of the species' range and 31 different haplotypes were obtained. The most frequent haplotype was Hap2, which was shared in all ten localities (132 individuals), whereas most haplotypes were rare and existed in only one or two individuals. Haplotype diversity ( h ) and nucleotide diversity (π) ranged from 0.338 to 0.731 and from 0.00058 to 0.00278, respectively, which represented a moderate level of haplotype diversity and a low level of nucleotide diversity. The genetic distance ranged from 0.0006 to 0.0028 within populations and from 0.0006 to 0.0023 between populations. An analysis of molecular variance and conventional population statistics ( F ST ) revealed a low level of genetic differentiation among ten populations ( F ST  = −0.00439, p  > 0.05), indicating that no significant population genetic structure existed in populations from the East China Sea and South China Sea. Both mismatch distribution and neutrality tests implied a recent population expansion event for the sesarmid crab species in the late Pleistocene.